2015
DOI: 10.1128/jb.02516-14
|View full text |Cite
|
Sign up to set email alerts
|

The Matrix Reloaded: How Sensing the Extracellular Matrix Synchronizes Bacterial Communities

Abstract: In response to chemical communication, bacterial cells often organize themselves into complex multicellular communities that carry out specialized tasks. These communities are frequently referred to as biofilms, which involve the collective behavior of different cell types. Like cells of multicellular eukaryotes, the biofilm cells are surrounded by self-produced polymers that constitute the extracellular matrix (ECM), which binds them to each other and to the surface. In multicellular eukaryotes, it has been e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
81
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(81 citation statements)
references
References 177 publications
(225 reference statements)
0
81
0
Order By: Relevance
“…A defining feature of biofilms is the presence of an extracellular matrix that binds the constituent cells together (Branda et al ., ; Steinberg and Kolodkin‐Gal, ). In our study, phase‐contrast microscopy revealed that the biofilm in the control group (cells cultured without Zn(II) exposure) consisted of bundled chains of cells, while in the 100 and 200 μM Zn(II) treatment groups, only dispersed, unclumped cells could be found (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A defining feature of biofilms is the presence of an extracellular matrix that binds the constituent cells together (Branda et al ., ; Steinberg and Kolodkin‐Gal, ). In our study, phase‐contrast microscopy revealed that the biofilm in the control group (cells cultured without Zn(II) exposure) consisted of bundled chains of cells, while in the 100 and 200 μM Zn(II) treatment groups, only dispersed, unclumped cells could be found (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For example, polysaccharides interact with proteins of the bacterial glycan synthesis and the export apparatus transferring them to the outer membrane leaflet or into extracellular space. 1 Furthermore, polysaccharide-protein complexes are found in interactions with host immune systems 2 , during biofilm formation 3 , and in pathogenesis, which emphasizes the important role of bacterial polysaccharides as vaccine targets. 4 In contrast to their ubiquitous relevance in biology, descriptions of these complexes on a molecular level are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…A common principle of all biofilms is the production of extracellular matrix (ECM) composed of different organic substances, such as extracellular proteins, exopolysaccharides and nucleic acids (Branda et al, 2005). While the ability to generate ECM appears to be a common feature of multicellular bacterial communities, the means by which these matrices are constructed and function are diverse (Branda et al, 2005;Steinberg and Kolodkin-Gal, 2015;Dragos and Kovacs, 2017).…”
Section: Biofilmsmentioning
confidence: 99%